Computational methods for fluid dynamics - Ferziger, Joel H.; Perić, M. (Milovan) 1957- (Springer, 2002)
Offers an overview of the techniques used to solve problems in fluid mechanics on computers and describes in detail those most often used in practice. Included are advanced techniques in computational fluid dynamics, like direct and large-eddy simulation of turbulence, multigrid methods, parallel computing, moving grids, structured, block-structured and unstructured boundary-fitted grids, free surface flows. This edition contains a new section dealing with grid quality and an extended description of discretization methods. The book also contains a great deal of practical advice for code developers and users, it is designed to be equally useful to beginners and experts. All computer codes can be accessed from the publisher's server ftp.springer.de on the Internet.